Impact of posterior septum resection on nasal airflow pattern and warming function. (2nd January 2020) - Li, Lifeng; London, Nyall R.; Zang, Hongrui; Han, Demin
Abstract: Background: The functional significance of the posterior segment of the septum is not fully understood. Aims/Objectives: The purpose of this study was to evaluate the impact of posterior septum resection with varying extents on nasal airflow pattern and warming function, and to determine the appropriate resection extent on posterior septum without disturbing airflow pattern. Material and Methods: Three dimensional models were established from the nasal CT scan of a healthy female volunteer without nasal disease. The models included the normal, as well as 1 cm, 2 cm, and 3 cm extent of posterior septum resection by virtual surgery. Using computational fluid dynamics, the airflow characteristics such as average and peak airflow velocity, average wall shear stress, average temperature and turbulence kinetic energy were recorded and compared among the four models. Results: By comparison with the normal model, the virtual surgeries with varying extents of posterior septum resection (1 cm, 2 cm, and 3 cm), demonstrated little alteration on indices of the average and peak airflow velocity, average wall shear stress, airflow temperature and turbulence kinetic energy. However, a statistical difference of the abovementioned indices existed when compared between varying planes of the nasal cavity ( p  < .001), although this did not appear to be significantly influenced by the degree of posterior septectomy. Conclusions and significance: From an aerodynamics perspective, little disturbance on airflow pattern and warming function of nasal cavity could be detected with increasing resection of posterior septum (up to 3 cm). These results may imply that resection of the posterior septum (up to 3 cm) has little impact on nasal function.